2012
DOI: 10.5194/cp-8-545-2012
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the ocean's role in glacial CO<sub>2</sub> reductions

Abstract: Abstract.A series of Last Glacial Maximum (LGM) marine carbon cycle sensitivity experiments is conducted to test the effect of different physical processes, as simulated by two atmosphere-ocean general circulation model (AOGCM) experiments, on atmospheric pCO 2 . One AOGCM solution exhibits an increase in North Atlantic Deep Water (NADW) formation under glacial conditions, whereas the other mimics an increase in Antarctic Bottom Water (AABW) associated with a weaker NADW. None of these sensitivity experiments … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 83 publications
8
43
0
Order By: Relevance
“…This supports previous model studies, which have identified GHG variations as an important contributor to Pleistocene glacial cycles (Gallée et al, 1992;Yoshimori et al, 2001;Ganopolski and Calov, 2011;AbeOuchi et al, 2013). And the results emphasize how important it is to identify the mechanisms responsible for the orbitalscale modulation of atmospheric CO 2 concentrations (Kohfeld and Ridgwell, 2009;Tagliabue et al, 2009;Chikamoto et al, 2012;Menviel et al, 2012;Brovkin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports previous model studies, which have identified GHG variations as an important contributor to Pleistocene glacial cycles (Gallée et al, 1992;Yoshimori et al, 2001;Ganopolski and Calov, 2011;AbeOuchi et al, 2013). And the results emphasize how important it is to identify the mechanisms responsible for the orbitalscale modulation of atmospheric CO 2 concentrations (Kohfeld and Ridgwell, 2009;Tagliabue et al, 2009;Chikamoto et al, 2012;Menviel et al, 2012;Brovkin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While the changes of earth's orbital and tilt parameters and the resulting shortwave radiative forcing at the top of the atmosphere are well understood, the carbon cycle feedbacks that led to the reconstructed atmospheric CO 2 changes are subject to ongoing research (Kohfeld and Ridgwell, 2009;Tagliabue et al, 2009;Brovkin et al, 2012;Chikamoto et al, 2012;Menviel et al, 2012). It was demonstrated, however, that the carbon cycle feedbacks played an important role during the last deglaciation and the Quaternary Period (last ∼ 2.6 million years), amplifying glacial-interglacial cycles (Gallée et al, 1992;Yoshimori et al, 2001;Ganopolski and Calov, 2011;Abe-Ouchi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The MIROC 3.2 contributed to the Coupled Model Intercomparison Project phase 3, which was extensively cited in the Intergovernmental Panel on Climate Change Fourth Assessment Report. The coefficient of the isopycnal layer thickness diffusivity was 7:0 3 10 26 cm 2 s 21 instead of the value of 3:0 3 10 26 cm 2 s 21 used in the original MIROC 3.2 (Oka et al 2011;Chikamoto et al 2012). The resolution of the atmospheric component was T42 (about 2.88 3 2.88) with 20 vertical levels, and that of the ocean component was about 1.48 3 18 with 43 vertical levels.…”
Section: B Description Of the Aogcm Experimentsmentioning
confidence: 99%
“…Brovkin et al, 2002;Bopp et al, 5 2003;Brovkin et al, 2007;Chikamoto et al, 2012;Palastanga et al, 2013;Schmittner and Somes, 2016;Buchanan et al, 2016) (Fig. 12).…”
Section: Ocean Primary Productivitymentioning
confidence: 99%
“…The most commonly accepted mechanisms to explain the atmospheric CO 2 decrease include lower sea surface temperatures (Martin et al, 2005;Menviel et al, 2012), iron fertilisation (Bopp et al, 2003;Oka et al, 2011;Jaccard et al, 2013;Ziegler et al, 2013;Martínez-Garcia et al, 2014;Lambert et al, 2015), sea-ice capping of air-sea gas exchange (Stephens and Keeling, 2000;Sun and Matsumoto, 2010;Chikamoto et al, 2012) and ocean circulation/stratification changes (Adkins et al, 2002;20 Lynch-Stieglitz et al, 2007;Skinner et al, 2010;Lippold et al, 2012;Gebbie, 2014;Skinner et al, 2014;Tiedemann et al, 2015;de la Fuente et al, 2015;Freeman et al, 2015), due to a range of possible mechanisms such as increased brine rejection (Shin et al, 2003;Bouttes et al, 2010Bouttes et al, , 2011Zhang et al, 2013;Ballarotta et al, 2014), a shift in/weakening of the westerly wind belt over the Southern Ocean (Toggweiler et al, 2006;Anderson et al, 2009;Völker and Köhler, 2013), stronger westerly winds over the North Atlantic (Muglia and Schmittner, 2015), and a reduced or reversed buoyancy flux from the 25 atmosphere to the ocean surface in the Southern Ocean (Watson and Garabato, 2006;Ferrari et al, 2014). A process that is conversely assumed to have contributed to increasing atmospheric CO 2 is increasing salinity and ocean total dissolved inorganic carbon (DIC) concentration in response to decreasing sea level (Ciais et al, 2013).…”
Section: Introductionmentioning
confidence: 99%